BIOGRAFI PROF. DR. H. M. DIAH Z, M.EdSEBAGAI TOKOH PENDIDIKAN RIAU - Anggraini, Resi Dewi; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Prof. Dr. H. M. Diah Z, M. Ed is an educational figure who has many roles in advancing education in Riau. The purpose of this study was to determine the educational history of Prof. Dr. H. M. Diah Z, M.Ed, to find out the role of Prof. Dr. H. M. Diah Z, M.E in advancing education, to find out the achievements of Prof. Dr. H. M. Diah Z, M.Ed and to find out the views of relatives and family towards the figure of Prof. Dr. H. M. Diah Z, M.Ed. The results of this study are Prof. Dr. H. M. Diah Z, M.Ed advancing education starting from being a teacher and lecturer, in collaboration with PT.CALTEX on the construction of the UNRI LANGUAGE LABORATORY, Following the Upgrading and Administration of Higher Education, as a facilitator in sending lecturers to take a Masters degree to a Foreign University. The method used in this research is qualitative. Data obtained from the interviews are supplemented with data obtained from books and data archives, then analyzed in their own language. The place of this research is in Pekanbaru. Data collection techniques used are documentation, interviews, observations and related literature in the Biography of Prof. Dr. H. M. Diah Z, M.Ed in advancing education in Riau.KeyWords: Biography, Educational Figure, Prof. Dr. H. M. Diah Z, M.Ed